Occurrence and seasonal variations of per- and polyfluoroalkyl substances (PFASs) including fluorinated alternatives in rivers, drain outlets and the receiving Bohai Sea of China. (December 2017) - Chen, Hong; Han, Jianbo; Zhang, Can; Cheng, Jiayi; Sun, Ruijun; Wang, Xiaomeng; Han, Gengchen; Yang, Wenchao; He, Xin
Abstract: A simultaneous sampling campaign was undertaken to study the pollution by 21 per- and polyfluoroalkyl substances (PFASs) in rivers, drain outlets and their receiving Bohai Sea of China. Chlorinated polyfluoroalkyl ether sulfonic acids (Cl-PFESAs) are being used as fluorinated alternatives and they were included in this study. In comparison with other regions and countries, high concentrations of ∑21 PFASs in seawater samples from the Bohai Sea, ranging from 5.03 to 41 700 ng/L (median: 64.8 ng/L), were observed. The spatial distribution of PFAS levels in this sea area was in the ranking of Laizhou Bay > Liaodong Bay > Bohai Bay > other sea areas. By comparing the levels and composition profiles of PFASs in the seawater and their sources (rivers and drain outlets), it was concluded that rivers and drain outlets are the primary sources of PFAS contamination to the Bohai Sea. These PFAS levels varied seasonally among the rivers and drain outlets, but statistically significant changes were not observed. Levels of 6:2 and 8:2 Cl-PFESAs in rivers, drain outlets and receiving sea were firstly reported in the present study. Relatively high concentrations of 6:2 Cl-PFESA were found in drain outlets, ranging from below method limits of quantification (MLQ) to 7600 ng/L, but 8:2 Cl-PFAES detection was infrequent and all median concentration below MLQ. Mass discharges to the sea of 6:2 Cl-PFESA from rivers and drain outlets to the sea were estimated to be 37 and 17 kg/y, respectively. Graphical abstract: Highlights: High concentrations of the total PFASs in seawater in the Bohai Sea were shown. Rivers and drain outlets were the primary sources of PFAS pollution in the Bohai Sea. Significant seasonal changes in PFAS levels from rivers and drain outlets were not observed. Levels of fluorinated alternatives in seawater and its sources were firstly reported. Mass discharges of 6:2 Cl-PFESAs from rivers and drain outlets were estimated. Abstract : Simultaneous survey of PFASs pollution including novel fluorinated alternatives (Cl-PFESAs) in rivers, drain outlets, and their receiving Bohai Sea were firstly and systematically investigated.